2019
DOI: 10.1103/physrevb.100.134102
|View full text |Cite
|
Sign up to set email alerts
|

Lattice dynamics and Raman spectrum of BaZrO3 single crystals

Abstract: BaZrO3 is a perovskite that remains in the simple cubic phase at all temperatures, hence with no first-order Raman-active phonon mode allowed by symmetry. Yet, it exhibits an intense Raman spectrum with sharp and well-defined features. Here, we report the evolution of the Raman spectrum of BaZrO3 single crystals in a broad temperature range (4-1200 K) and discuss its origin with the support of detailed first-principle calculations of the lattice dynamics. Phonon calculations are performed not only for the cubi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
36
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 53 publications
4
36
0
Order By: Relevance
“…Indeed, neutron powder diffraction measurements demonstrated that BaZrO 3 retains Pm 3m symmetry down to temperatures near absolute zero, a rare case among perovskite-structured compounds [8][9][10]. Nevertheless, several ab initio theoretical calculations suggested the existence of a structural instability associated with octahedral rotations [8,[11][12][13][14]. An apparent discrepancy between the computational predictions and experiments has been reconciled by hypothesizing these structural distortions to be correlated only over the local scale, thus remaining undetectable by Bragg diffraction.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, neutron powder diffraction measurements demonstrated that BaZrO 3 retains Pm 3m symmetry down to temperatures near absolute zero, a rare case among perovskite-structured compounds [8][9][10]. Nevertheless, several ab initio theoretical calculations suggested the existence of a structural instability associated with octahedral rotations [8,[11][12][13][14]. An apparent discrepancy between the computational predictions and experiments has been reconciled by hypothesizing these structural distortions to be correlated only over the local scale, thus remaining undetectable by Bragg diffraction.…”
Section: Introductionmentioning
confidence: 99%
“…BaZrO 3 exhibits prominent Raman spectra despite first-order scattering in cubic perovskites prohibited by symmetry. Recent studies of BaZrO 3 single crystals [14] attributed these spectral features to second-order events with no signs of phase transitions down to low temperatures; nevertheless, the authors speculated that such second-order Raman scattering could be linked to some kind of structural disorder. An absence of phase transitions at low temperatures has also been conjectured from inelastic neutron-scattering measurements performed on powder samples [9], which suggested that the energy and width of a feature assumed to represent the R 25 phonon associated with out of phase octahedral rotations remain approximately constant between 500 and 5 K. However, these analyses relied on several assumptions and fitting of spectral features exhibiting a significant overlap.…”
Section: Introductionmentioning
confidence: 99%
“…experimental a 0 3.195 Å (Fig. 2.c) and lattice dynamics reported in our previous work [36] -correcting the reported overestimation within the more conventional Perdew-Burke-Ernzerhof (PBE) functional [31]. Norm-conserving pseudopotentials [48] have been employed with the following orbitals considered as the valence states: 5s, 5p, and 6s for Ba 4s, 4p, 4d, and 5s for Zr, and 2s and 2p for O.…”
Section: Methods and Experimental Detailsmentioning
confidence: 64%
“…Besides, unlike in SrTiO 3 and CaTiO 3 [34,35] where the polar instability at the zone center plays a major role, only the zone boundary tilt mode is unstable in BaZrO 3 which makes it a comparatively "pure" tilt system. Finally it has been shown that several antiferrodistortive phases are nearly degenerate at ambient pressure [36], specifically the tetragonal I4/mcm (a 0 a 0 c − in Glazer notation), the orthorhombic Imma (a − b 0 a − ) and the rhombohedral R 3c (a − a − a − ). This situation leaves the energy landscape particularly open for the stabilization of multiple phases and the existence of multiple phase transitions under pressure.…”
Section: Introductionmentioning
confidence: 99%
“…The Raman spectrum broadening observed here could be related to the presence of defects and distortions in the cubic crystalline lattice of these NPs, where low-symmetry phases co-exist with distorted octahedra, and to the combination of bands and second-order overtones. Overtones are always Raman-allowed, and the broad Raman bands are Raman-active according to the direct product of the irreducible representations associated with the respective phonon vibration modes ( Toulouse et al . , 2019 ).…”
Section: Resultsmentioning
confidence: 99%